Gut Microbiota Dysbiosis Influences Metabolic Homeostasis in Spodoptera frugiperda - Chen, Yaqing; Zhou, Huanchan; Lai, Yushan; Chen, Qi; Yu, Xiao-Qiang; Wang, Xiaoyun (Frontiers in Microbiology, 2021)
Insect gut microbiota plays important roles in acquiring nutrition, preventing pathogens infection, immune responses, and communicating with environment. Gut microbiota can be affected by some external factors such as foods and antibiotics. Spodoptera frugiperda (Lepidoptera: Noctuidae) is an important destructive pest of grain crops all over the world. The function of gut microbiota in S. frugiperda remains to be investigated. In this study, we fed the S. frugiperda with antibiotic mixture (penicillin, gentamicin, rifampicin, and streptomycin) to perturb the gut microbiota, and further examined the effect of dysbiosis in gut microbiota on the gene expression of S. frugiperda by RNA sequencing. We found the composition and diversity of gut bacterial community were changed in S. frugiperda after antibiotics treatment. The Firmicutes, Protecobactera, Bacteroidetes, Actinobacteria phyla were the most dominant in S. frugiperda. After antibiotics treatment, the Firmicutes was decreased, and abundance of Enterococcus and Weissella genera were dramatically reduced. Transcriptome analysis showed that 1,394 differentially expressed transcripts (DETs) were found between the control and antibiotics group. The Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) results showed that antibiotics-induced dysbiosis affected many biological processes, such as energy production, metabolism and autophagy-lysosome signal pathway. Our results indicated that dysbiosis of gut microbiota by antibiotics exposure affects energy and metabolic homeostasis in S. frugiperda, and our work help understand the role of gut microbiota in insects.